Acetyl coenzyme A kinetic studies on N-acetylation of environmental carcinogens by human N-acetyltransferase 1 and its NAT1*14B variant - Habil, Mariam R.; Doll, Mark A.; Hein, David W. (Frontiers in Pharmacology, 2022)
N-acetyltransferase 1 (NAT1) is a xenobiotic metabolizing enzyme that uses acetyl coenzyme A (AcCoA) as a cofactor for N-acetylation of many carcinogens including aromatic amines and alkylanilines. NAT1 is characterized by single nucleotide polymorphisms or (SNPs) that may modulate affinity towards AcCoA. In the current study, we used Chinese hamster ovary (CHO) cells stably transfected with human NAT1*4 (reference allele) or NAT1*14B (variant allele) to measure AcCoA kinetic parameters for N-acetyltransferase activity measurements towards p-aminobenzoic acid (PABA), 4-aminobiphenyl (ABP), β-naphthylamine (BNA), benzidine and 3,4-dimethylaniline (3,4-DMA). Our results showed higher N-acetylation rates for each substrate catalyzed by NAT1*4 compared to NAT1*14B. NAT1*4 exhibited higher affinity to AcCoA when catalyzing the N-acetylation of BNA and benzidine compared to NAT1*14B. The results of the current study provide further insights into differences in carcinogen metabolism among individuals possessing the NAT1*14B haplotype.